Tracked Changes. Portable fire extinguishers. Requirements for the construction, pressure resistance and mechanical tests for extinguishers with a maximum allowable pressure equal to or lower than 30 bar, which comply with the requirements of EN 3-7 Part 8, (6th June 2022) - British Standards Institution,
No abstract available